2006
DOI: 10.2166/wst.2006.198
|View full text |Cite
|
Sign up to set email alerts
|

Solutions to a combined problem of excessive hydrogen sulfide in biogas and struvite scaling

Abstract: The Woodman Point Wastewater Treatment Plant (WWTP) at Western Australia has experienced two separate problems causing avoidable maintenance costs, the build-up of massive struvite (MgNH 4 PO 4 . 6H 2 O) scaling downstream of the anaerobic digester and the formation of hydrogen sulfide (H 2 S) levels in the digester gas to levels that compromised gas engine operation and caused high operating costs on the gas scrubber. As both problems hang together with a chemical imbalance in the anaerobic digester, we decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…9-10). In contrast to vivianite, struvite is observed in sulfide-rich waste water (e.g., Charles et al, 2006) and may thus be stable in the presence of sulfide. This is confirmed by our sulfidization experiment, in which, for example, only 25 % of precipitate 4 (estimated struvite fraction: 20 mol% P) dissolved in sulfide-rich seawater (Fig.…”
Section: +3000 Yearsmentioning
confidence: 99%
“…9-10). In contrast to vivianite, struvite is observed in sulfide-rich waste water (e.g., Charles et al, 2006) and may thus be stable in the presence of sulfide. This is confirmed by our sulfidization experiment, in which, for example, only 25 % of precipitate 4 (estimated struvite fraction: 20 mol% P) dissolved in sulfide-rich seawater (Fig.…”
Section: +3000 Yearsmentioning
confidence: 99%
“…Increased struvite formation in the digester is advantageous since its formation decreases the recycling of ammonia and phosphorous back to the wastewater treatment process, however, in practice, many WWTPs experience problems with struvite precipitation in the centrifuges and pipe network resulting in significant maintenance costs (Charles et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Sattler and Rosenberk (2006) initial concentration greatly influence the efficiency of the process. Charles et al (2006) present results that showed that, the hydrogen sulfide emission in digesters could be effectively and economically controlled by the addition of iron dosing. Slightly higher than the theoretical value of 1.5 mol of FeCl3 was required to precipitate 1 mol of dissolved sulfide inside the digester.…”
Section: Odor Case Studiesmentioning
confidence: 71%